PROFESIONALITAS GURU PAI DALAM PENGELOLAAN PEMBELAJARAN DI SMA NEGERI 6 YOGYAKARTA - Nofiaturrahmah, Fifi (Pascasarjana IAIN Kudus, 2017)
In Learning takes creativity of teachers in the development of standards and basic competencies. Support principals, teachers and support colleagues internally within the teacher is indispensable in learning PAI. Islamic Education Teachers In senior high school 6 Yogyakarta've been able to manage learning well. With the mastery of information technology teachers PAI able to choose the right strategy and media in learning. Complete learning strategies to help overcome the differences found in the student and sufficient means also supports the management of learning. Teachers not only to plan a lesson but also to be able to perform well and structured. Factors that support the ability of teachers PAI most dominant learning PAI is MGMP. The limiting factor is the lack of teacher knowledge about PAI SBC.